PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP BIAYA MODAL DENGAN SUSTAINABILITY ASSURANCE DAN PENYEDIA ASSURANCE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan yang terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Munika Murthin; Aditya Septiani (Diponegoro Journal of Accounting, 2022)
The purpose of this research is to examine the effect of sustainability report disclosure on cost of capital with sustainability assurance and assurance provider as moderating variable. The variables used in this research are the dependent variable (cost of capital), independent variable (sustainability report), moderating variable (sustainability assurance, assurance provider), and control variable (company size and company leverage).This population in this research are companies listed on the Indonesia Stock Exchange in 2018-2020. Sampling based on purposive sampling method that follows certain criteria samples obtained were 108 companies for the three years obtained (2018-2020). The analytical method used in this research is multiple regression analysis.The result of this research indicate that the sustainability report disclosure has no effect on the cost of capital. While, the sustainability report disclosure has no effect on the cost of capital which is moderated by sustainability assurance. While, the sustainability report disclosure has no effect on the cost of capital moderated by the assurance provider.